Oral cancer in young adults: incidence, risk factors, prognosis, and molecular biomarkers - Lenoci, Deborah; Moresco, Elisa; Cavalieri, Stefano; Bergamini, Cristiana; Torchia, Erica; Botta, Laura; Canevari, Silvana; Trama, Annalisa; Licitra, Lisa; De Cecco, Loris (Frontiers in Oncology, 2024)
Oral cavity squamous cell carcinoma (OCSCC) predominantly affects the tongue and the floor of the mouth, primarily in patients over 50 years of age. Incidence and mortality rates vary significantly worldwide, influenced by geographic areas and demographic characteristics. Epidemiological studies revealed an increase in incidence of OCSCC among young adults (YA) <44 years old. This narrative review, provides updated information on the incidence, risk factors, and prognosis of YA-OCSCC using data published from 2018 to 2023 from different geographic locations. The studies indicate that the incidence of YA-OCSCC in Asia is approximately twice that in the US and that the incidence is strongly linked to risk factors such as betel quid chewing, tobacco use, and high alcohol consumption. The prognosis for YA-OCSCC, compared to that in older patients, shows similar or better overall survival, even in cases with relapses, but worse 5-year disease-free survival, despite receiving similar treatments. Consequently, a concerted effort is crucial to raise awareness about the cessation of tobacco and areca nut use, alcohol control, and the promotion of healthy lifestyle behaviors. Recent molecular data on YA-OCSCC suggests a potential profile characterized by epidermal growth factor receptor overexpression, low tumor mutation burden and an attenuated immune response. Upon confirmation in larger cohorts of YA-OCSCC patients from different geographical areas, the validated markers could aid in selecting tailored treatments.